Integrating Literacy and Islamic Values: The Rotating Islamic Book Week at TK Yaa Bunayya to Enhance Children’s Language Development - Rahman, Amatur; Harmanto, Bambang; Rahmawati, Ida Yeni (AT-TURATS, 2025)
This study aims to describe the implementation of the rotating Islamic-themed book week program as a form of literacy-based Islamic education practice in stimulating early childhood language skills at TK Yaa Bunayya Magetan. The program is designed to strengthen collaboration between school and family through the activity of borrowing Islamic storybooks to be read together with parents at home. This activity not only aims to foster reading interest but also to instill Islamic values that shape character and enrich children's vocabulary. The research employs a descriptive qualitative approach with data collected through observation, interviews, and documentation. The research subjects include the school principal, classroom teacher, assistant teacher, and students. The findings show that the program is effective in enhancing children's speaking skills, expanding language comprehension, and strengthening verbal expression. Active interaction between children and parents during reading becomes a key moment in the scaffolding process and supports development within the child's zone of proximal development, as explained by Vygotsky and Bruner. The results have important implications for the development of literacy-based learning models that integrate Islamic values, both theoretically and practically in early childhood education settings. This study highlights the necessity of active collaboration between schools and families to support children's language and character development, offering practical guidance for teachers and parents in implementing effective literacy strategies.Penelitian ini bertujuan untuk mendeskripsikan pelaksanaan program pekan buku bertema Islami bergilir sebagai praktik pendidikan berbasis literasi Islami dalam menstimulasi kemampuan berbahasa anak usia dini di TK Yaa Bunayya Magetan. Program ini dirancang untuk memperkuat kolaborasi antara sekolah dan keluarga melalui aktivitas peminjaman buku cerita Islami yang dibaca bersama orang tua di rumah. Kegiatan ini tidak hanya bertujuan untuk menumbuhkan minat baca, tetapi juga menanamkan nilai-nilai Islami yang membentuk karakter dan memperkaya kosakata anak. Penelitian menggunakan pendekatan kualitatif deskriptif dengan pengumpulan data melalui observasi, wawancara, dan dokumentasi. Subjek penelitian meliputi kepala sekolah, guru kelas, guru pendamping, dan siswa. Temuan menunjukkan bahwa program ini efektif dalam meningkatkan keterampilan berbicara anak, memperluas pemahaman bahasa, dan memperkuat ekspresi verbal. Interaksi aktif antara anak dan orang tua saat membaca menjadi momen penting dalam proses scaffolding dan mendukung perkembangan dalam zona perkembangan proksimal anak, sebagaimana dijelaskan oleh Vygotsky dan Bruner.Hasil penelitian ini memiliki implikasi penting untuk pengembangan model pembelajaran berbasis literasi yang mengintegrasikan nilai-nilai Islami, baik dalam kerangka teori maupun praktik pendidikan di lembaga pendidikan anak usia dini. Temuan ini menegaskan perlunya kolaborasi aktif antara sekolah dan keluarga dalam mendukung perkembangan bahasa dan karakter anak, serta memberikan pedoman bagi guru dan orang tua dalam menerapkan strategi literasi yang efektif.